Adenoids with Glue Ear: Incidence, Management and Outcome (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: glue ear or otitis media with effusion (OME); adenoids; pure tone audiometry (PTA); impedance audiometry; or tympanometry; otoscopy